Odpowiedź :
Odpowiedź:
a) (-8)*6= - 48
b) (-74):(-2)= 37
c) 56 : (-7)= - 8
d) (-9)* (-3)= 27
e) 3*( -4) -2*(-5)= -12 +10= - 2
f) ( -64) : 8*2 :( -4)= - 8*2 :(-4)= -16 : (-4)= 4
zad.2
a) 5-9= - 4
b) 7- (-6)= 7 +6= 13
c) ( - 3 ) - 8= - 3 - 8 = - 11
d) (-2)- (-4)= -2 +4= 2
e) ( - 12 ) - (-6) + (-8)= -12 +6 -8= -6-8= - 14
Szczegółowe wyjaśnienie:
Odpowiedź:
[-8]*6=-48: - jest dlatego że 8 jest większe niż 6
[-74]:[-2]= 37
56:[-7]=-8
(-9). 1-3) =-12
3.(-4)-2.(-5) =-2
(-64): 8.2:(-4)=4
ODEJMOWANIE
5 - 9 =-4
7- (-6)=13
(-3)-8=-11
(-2)-(-4)=2
(-12)-(-6)+(-8) =-14
pls daj naj
Szczegółowe wyjaśnieni